(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background. Childhood obesity is associated with enormous health consequences and costs to society. This study aims to systematically review the studies on Cost Effectiveness Analysis (CEA) of primary prevention programmes of childhood obesity, discussing the gaps and providing recommendations for future research. Methods. All the studies on the cost effectiveness evaluation of primary prevention of obesity among children were included. Studies were retrieved from MEDLINE and Google Scholar, up to 31st March 2012, with only English language papers being eligible. The quality of the retrieved studies was evaluated by using the Drummond scale. Results. Eight studies were included, five of which concerning community-based intervention programmes, while three school-based programmes. Fifty-percent of the studies, 3 school-based and 1 community-based primary prevention programme reported the intervention being cost effective. The studies were heterogeneous in terms of study design, quality, target population and outcome measures. Use of the Drummond scale showed that the eight studies were of low-medium quality. Conclusion. Although model-based studies may be considered as practical measures applicable to different type of programmes and settings, we auspicate for a convergence towards the use of homogenous clinical and outcome measures in order to properly evaluate the added value of obesity primary prevention programmes in childhood